Translation and the poet's life the ethics of translating in English culture, 1646-1726 - Davis, Paul 1968- (Oxford, New York Oxford University Press, 2008)
Paul Davis explores the personal and cultural significances of translating as a distinctive mode of imaginative conduct for the five principal poet-translators of what was the golden age of the art in England: John Denham, Henry Vaughan, Abraham Cowley John Dryden, and Alexander Pope.
Electronic reproduction.
Keywords: English poetry -- History and criticism. -- Early modern, 1500-1600.; English poetry -- History and criticism. -- 18th century; Classical poetry -- Translations into English -- History and criticism; Translators -- History -- 17th century. -- England; Translators -- History -- 18th century. -- England; Poets, English -- Early modern, 1500-1700.; Poets, English -- 18th century; Translating and interpreting -- Moral and ethical aspects